Early Psychosis Intervention-Spreading Evidence-based Treatment (EPI-SET): protocol for an effectiveness-implementation study of a structured model of care for psychosis in youth and emerging adults. Issue 6 (3rd June 2020) - Kozloff, Nicole; Foussias, George; Durbin, Janet; Sockalingam, Sanjeev; Addington, Jean; Addington, Donald; Ampofo, Augustina; Anderson, Kelly K; Barwick, Melanie; Bromley, Sarah; Cunningham, Jasmyn E A; Dahrouge, Simone; et al.
Abstract : Introduction: While early psychosis intervention (EPI) has proliferated in recent years amid evidence of its effectiveness, programmes often struggle to deliver consistent, recovery-based care. NAVIGATE is a manualised model of EPI with demonstrated effectiveness consisting of four components: individualised medication management, individual resiliency training, supported employment and education and family education. We aim to implement NAVIGATE in geographically diverse EPI programmes in Ontario, Canada, evaluating implementation and its effect on fidelity to the EPI model, as well as individual-level outcomes (patient/family member-reported and interviewer-rated), system-level outcomes (captured in provincial administrative databases) and engagement of participants with lived experience. Methods and analysis: This is a multisite, non-randomised pragmatic hybrid effectiveness-implementation type III mixed methods study coordinated at the Centre for Addiction and Mental Health (CAMH) in Toronto. Implementation is supported by the Provincial System Support Program, a CAMH-based programme with provincial offices across Ontario, and Extension of Community Healthcare Outcomes Ontario Mental Health at CAMH and the University of Toronto. The primary outcome is fidelity to the EPI model as measured using the First Episode Psychosis Services—Fidelity Scale. Four hundred participants in the EPI programmes will be recruited and followed using both individual-level assessments and health administrative data for 2 years following NAVIGATE initiation. People with lived experience will be engaged in all aspects of the project, including through youth and family advisory committees. Ethics and dissemination: Research ethics board approval has been obtained from CAMH and institutions overseeing the local EPI programmes. Study findings will be reported in scientific journal articles and shared with key stakeholders including youth, family members, programme staff and policymakers. Trial registration number: NCT03919760; Pre-results .